Lithography-free variation of the number density of self-catalyzed GaAs nanowires and its impact on polytypism. (1st August 2018) - Schroth, Philipp; Jakob, Julian; Feigl, Ludwig; Kashani, Seyed Mohammad Mostafavi; Pietsch, Ullrich; Baumbach, Tilo
Abstract: Abstract : We investigate the impact of increasing number density of self-catalyzed GaAs nanowires (NWs) on their crystal structure, grown by molecular beam epitaxy. To this end, we employ an iterative, lithography-free approach for varying the number density of self-catalyzed GaAs NWs grown on Si(111) covered with native oxide. We use scanning electron microscopy and x-ray diffraction in combination with simulations based on the extended Markov model for the morphologic characterization of the so obtained NWs. Our findings show how both the shape of the Ga-droplet and the NW crystal structure are affected even by relatively small changes of the wire number density, allowing for a quantification of its influence on the local NW growth conditions at nominally identical growth parameters.